INFLUENCE OF VIDIO MEDIA ON LEARNING AND TECHNIQUES EXERCISE ON BADMINTON LEARNING OUTCOMES STUDENTS AT SMA N 2 MEDAN TP 2023/2024: PENGARUH MEDIA VIDIO PEMBELAJARAN DAN TEKNIK LATIHAN TERHADAP HASIL BELAJAR BULU TANGKIS SISWA DI SMA N 2 MEDAN TP 2023/2024 - Sri Wahyuni, Ade (LPPM UPMI, 2023)
This research aims to find out the influence of learning video media and training techniques on student badminton learning outcomes at SMA N 2 MEDAN TP 2023/2024. This type of research is experimental research. This research aims to prove the effect of training using Badminton Media on Student Badminton Learning Outcomes. The population used in this research was 60 people. In this research, from a population of 60 players, 30 players were selected by sampling using a purposive sample. The data collection technique in this research used a test of dribbling the ball through the stake. The data that will be collected in this research is Pre-test data on dribbling the ball through the stakes before the sample is given treatment, and Post-test data after the sample is given treatment using Learning Video Media. This research uses experimental methods. analysis of research data by comparing pre-test and post-test data after being given treatment. If the calculated t value is smaller than the t table value then Ha is rejected and if the calculated t value is greater than t table then Ha is accepted. The formula used in this research is the t-test. The influence of training techniques on student learning outcomes can be seen from the hypothesis test above. Based on the results of the separate group t test, during the posttest it turned out that the learning outcomes of the experimental class students were higher than the learning outcomes of the control class students, it can be seen from the average score of the experimental class being higher than the average score of the control class (87.5 > 76.5).